Elementary theory of cubics and quartics - Mačys, Juozas Juvencijus (Lietuvos matematikos rinkinys, 2017)
It is proved that cubic and quartic equations in real numbers can be solvedelementarily, avoiding complex numbers and derivatives. Corresponding algorithms are presented.
Keywords: cubic equation; quartic equation; rational solutions; factorization